2015
DOI: 10.1039/c5ta05231a
|View full text |Cite
|
Sign up to set email alerts
|

Repelling hot water from superhydrophobic surfaces based on carbon nanotubes

Abstract: Superhydrophobic (SH) surfaces generally refer to those having a static water contact angle larger than 150° and a slide angle less than 10°, when both the surface and the water droplet are at room temperature. Most such surfaces lose superhydrophobicity when exposed to hot (e.g., >55 o C) water.Our recently published results (Z. indicated that hot water superhydrophobicity is maintained when the SH surface temperature is higher than that of the water droplet. Here, we find that carbon nanotubes (CNTs) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…However, there are few works reporting on such type superhydrophobic surface. Yang and co‐workers constructed a hot water‐repellent superhydrophobic surfaces based on carbon nanotubes and organic silicone resin. The as‐prepared surfaces maintained their low SAs (<5°) but their CAs fell to ≈145°, i.e., losing the superhydrophobicity, when the temperature of water droplet was higher than 30 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few works reporting on such type superhydrophobic surface. Yang and co‐workers constructed a hot water‐repellent superhydrophobic surfaces based on carbon nanotubes and organic silicone resin. The as‐prepared surfaces maintained their low SAs (<5°) but their CAs fell to ≈145°, i.e., losing the superhydrophobicity, when the temperature of water droplet was higher than 30 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements of CAs and SAs for hot water were slightly different from that for room‐temperature water and more details can be found in ref. . As the temperature of hot liquid drops decreases quickly, it is difficult to get the real temperature of hot water droplets on the surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have mainly been focused on the fabrication of hot-water super-repellent surfaces, such as by spray coating, deposition, and electrophoresis-assisted coating, and their applications for self-cleaning and oil/water separation, [7][8][9][10][11][12][13][14][15] whereas only a few studies have reported on wetting mechanisms by hot water. Despite its importance, the effort to study the mechanisms of super-repellency to hot liquids appears very limited.…”
mentioning
confidence: 99%
“…Previous studies have mainly been focused on the fabrication of hot-water super-repellent surfaces, such as by spray coating, deposition, and electrophoresis-assisted coating, and their applications for self-cleaning and oil/water separation, [7][8][9][10][11][12][13][14][15] whereas only a few studies have reported on wetting mechanisms by hot water. Previous studies have mainly been focused on the fabrication of hot-water super-repellent surfaces, such as by spray coating, deposition, and electrophoresis-assisted coating, and their applications for self-cleaning and oil/water separation, [7][8][9][10][11][12][13][14][15] whereas only a few studies have reported on wetting mechanisms by hot water.…”
mentioning
confidence: 99%
“…In addition, many superhydrophobic/superoleophilic materials exhibited low repellency against hot water of 50 °C or higher . It has been recently reported that candle soot and silica‐coated suerhydrophobic/superoleophilic meshes could repel hot water of 92 °C .…”
mentioning
confidence: 99%